A Study of dynamic behavior on concrete structures ( Bridge ) / Norrizan Ismail (Faculty of Civil Engineering, 1992)
Dynamic effects on building structures caused by seismicity, wind, impact and vibrations, sophisticated tools have been developed, particularly using variational method such as Finite or Boundary Element Methods for a better understanding of the structural behaviour,the optimization of the design and the prediction of failure under dynamic loading. Experimental investigations in conjunction with system identification provide the basis to develop and verify theoretical models both for the structure and the material properties.